The dynamic landscape of transcription initiation in yeast mitochondria - Byeong-Kwon Sohn (Nature Portfolio, 2020)
Conformational dynamics during the early stage of transcription is crucial to understanding the regulation of transcription efficiency and fidelity. Here the authors, by single-molecule fluorescence resonance energy transfer approaches, examine the conformational dynamics of the two-component transcription system of yeast mitochondria with single-base resolution.